The effects of virtual reality as a physiotherapeutic treatment in patients with multiple sclerosis: An integrative review of the literature (Research, Society and Development, 2023)
To analyze the effects of virtual reality as a physiotherapeutic treatment in patients with multiple sclerosis. Methodology: This is an integrative review of the literature that was searched in the Pubmed/MEDLINE, PEDro, Lilacs, IBECS and Scielo databases. The PICO strategy was used to develop the research question and included studies with free full text, published between 2013 and 2023, in Portuguese, English and Spanish. The study included five articles. Although more research is needed, this study provided evidence that the use of VR for the MS population can improve autonomy and independence in activities of daily living for MS patients. VR-based treatment in patients with multiple sclerosis is of great relevance for optimizing conventional treatment so that it has positive effects in the rehabilitation of functional deficits.